Modified cobaltosic oxide precursor material and preparation method and application thereof

By doping nickel, manganese and aluminum elements and preparing modified cobalt tetroxide precursor materials, the problems of existing materials being broken and cracked at high voltages are solved, and the cycle stability and life of lithium cobalt oxide cathode material is significantly improved.

CN119461499APending Publication Date: 2025-02-18QUZHOU HUAYOU COBALT NEW MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411815069.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing modified cobalt tetraoxide materials are prone to breaking and cracking at high voltages, resulting in a significant reduction in the cycle life and cycle stability of lithium cobalt oxide positive electrode materials.

Method used

By doping nickel, manganese and aluminum elements and limiting their molar proportions, a modified cobalt tetroxide precursor material with a D50 particle size of 15 to 20 μm and a specific surface area of ​​3 to 5 m2/g was prepared, using specific nucleation and The growth process and the heating sintering method ensure uniform particle size of the material and no cracking on the particle surface.

Benefits of technology

It effectively stabilizes the lattice structure of the precursor material, reduces the risk of particle crushing, and improves the cycle stability and cycle life of lithium cobalt oxide positive electrode material at high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461499A_ABST
    Figure CN119461499A_ABST
Patent Text Reader

Abstract

The invention discloses a modified cobaltosic oxide precursor material and a preparation method and application thereof, and relates to the technical field of lithium ion batteries, the modified cobaltosic oxide precursor material comprises a cobaltosic oxide matrix, and a nickel element and a manganese element doped in the cobaltosic oxide matrix; wherein in metal elements of the modified cobaltosic oxide precursor material, the molar ratio of a nickel element is 5%-20%, the molar ratio of a manganese element is 1%-3%, the molar ratio of an aluminum element is 0.8%-3%, the D50 particle size of the modified cobaltosic oxide precursor material is 15-20 microns, the specific surface area of the modified cobaltosic oxide precursor material is 3-5 m < 2 > / g, and the particle size distribution width SPAN value of the modified cobaltosic oxide precursor material is 0.2-0.4. The precursor has the advantages of uniform particle size, no cracking on the particle surface and the like, and the lithium cobalt oxide positive electrode material prepared from the precursor material has excellent cycle stability and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a modified cobalt oxide precursor material and a preparation method and application thereof. Background Art

[0002] As a key component of lithium-ion batteries, positive electrode materials play a decisive role in the performance and cost of batteries. Lithium cobalt oxide positive electrode materials are widely used in the 3C technology field due to their advantages such as high safety and high energy density. The energy density of the battery can be further improved by increasing the charging cut-off voltage of lithium cobalt oxide, but the structure of lithium cobalt oxide is prone to collapse under high voltage, and the capacity decays rapidly, resulting in a significant reduction in cycle life and cycle stability.

[0003] The precursor material of lithium cobalt oxide is cobalt tetroxide, and the physical and chemical properties of cobalt tetroxide will directly affect the electrochemical properties of lithium cobalt oxide. At present, most cobalt tetroxide is doped or coated to improve its stability under high voltage, but the improvement is limited. The modified cobalt tetroxide particles are prone to cracking and produce broken small particles. Summary of the invention

[0004] The main purpose of the present invention is to provide a modified cobalt oxide precursor material and a preparation method and application thereof, so as to solve the problems of fragmentation and cracking of the existing modified cobalt oxide material.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a modified cobalt tetroxide precursor material, which comprises a cobalt tetroxide matrix and nickel, manganese and aluminum elements doped into the cobalt tetroxide matrix; wherein, among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of the nickel element is 5% to 20%, the molar proportion of the manganese element is 1% to 3%, and the molar proportion of the aluminum element is 0.8% to 3%, the D50 particle size of the modified cobalt tetroxide precursor material is 15 to 20 μm, and the specific surface area is 3 to 5 m 2 / g, and the particle size distribution width SPAN value of the modified cobalt tetroxide precursor material is 0.2-0.4.

[0006] Further, among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of nickel element is 12% to 20%; and / or, among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of cobalt element is 60% to 95%; and / or, the modified cobalt tetroxide precursor material also includes aluminum element doped into the cobalt tetroxide matrix; among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of aluminum element is 0.8% to 3%; and / or, the tap density of the modified cobalt tetroxide precursor material is 2 to 3 g / cm 3 .

[0007] Further, the chemical formula of the modified cobalt oxide precursor material is (Co x Ni y Mn y Al k )3O4, wherein: x+y+z+k=1, 0.76≤x≤0.92, 0.05≤y≤0.2, 0.01≤z≤0.03, 0.02≤k≤0.03.

[0008] Further, in the metal elements of the modified cobalt tetroxide precursor material, the molar ratio of cobalt element is 76.2% to 81.8%, the molar ratio of nickel element is 12.7% to 18.6%, the molar ratio of manganese element is 2.8% to 3%, and the molar ratio of aluminum element is 2.3% to 2.6%; and / or, the D50 particle size of the modified cobalt tetroxide precursor material is 16 to 17 μm; and / or, the tap density of the modified cobalt tetroxide precursor material is 2.6 to 2.7 g / cm 3 ; and / or, the specific surface area of ​​the modified cobalt tetroxide precursor material is 3.8 to 4 m 2 / g; and / or, the SPAN value of the modified cobalt tetroxide precursor material is 0.28-0.32.

[0009] The second aspect of the present invention provides a method for preparing the modified cobalt trioxide precursor material of the first aspect, comprising the following steps:

[0010] S1, respectively adding a metal salt solution and a carbonate solution into a reaction bottom liquid, and performing nucleation by a first speed reduction method to obtain a first reaction liquid; wherein the D50 particle size of the solid phase material in the first reaction liquid is 8 to 12 μm;

[0011] S2, adding a metal salt solution and a carbonate solution to the first reaction solution, and growing the solution by a second method of reducing the rotation speed and flow rate to obtain a second reaction solution; wherein the D50 particle size of the solid phase material in the second reaction solution is 20 to 25 μm;

[0012] S3, washing, centrifuging and drying the second reaction liquid in sequence to obtain a dry product; sintering the dry product at a high temperature to obtain a modified cobalt tetroxide precursor material;

[0013] The metal salt solution contains cobalt salt, aluminum salt, nickel salt and manganese salt.

[0014] Furthermore, the first speed reduction is that the speed decreases by 20 rpm for every 1.5-2.0 μm increase in the D50 particle size of the solid phase material in the reaction solution;

[0015] The second speed reduction flow rate is that the speed decreases by 15 rpm and the flow rate of the metal salt solution decreases by 10 mL / min for every 1-1.5 μm increase in the D50 particle size of the solid phase material in the reaction solution;

[0016] Preferably, during the nucleation process, the rotation speed is 150 to 250 rpm and the flow rate of the metal salt solution is 10 to 40 mL / min;

[0017] Preferably, during the growth process, the rotation speed is 80 to 150 rpm and the flow rate of the metal salt solution is 10 to 60 mL / min;

[0018] Preferably, during the nucleation process, the reaction temperature is 35-45°C and the pH value is controlled to be 7.5-8.5;

[0019] Preferably, during the growth process, the reaction temperature is 35-45°C and the pH value is controlled to be 7-8;

[0020] Preferably, the pH value of the reaction base solution is 7 to 9;

[0021] Preferably, the D50 particle size of the solid phase material in the first reaction solution is 8.5 to 9.5 μm;

[0022] Preferably, the D50 particle size of the solid phase material in the second reaction liquid is 20-22 μm.

[0023] Furthermore, the temperature-raising sintering is sequentially sintering in the first temperature zone, the second temperature zone and the third temperature zone; the temperature of the third temperature zone is greater than the temperature of the second temperature zone and greater than the temperature of the first temperature zone;

[0024] Preferably, the temperature of the first temperature zone is 300-450°C, the temperature of the second temperature zone is 450-600°C, and the temperature of the third temperature zone is 780-820°C.

[0025] Further, the metal salt solution and the carbonate solution are fed in parallel through the upper and lower paths of the reactor; and / or,

[0026] During the nucleation and growth process, when the total volume of the reaction liquid reaches 80% to 90% of the reactor volume, the feeding is stopped, part of the supernatant is extracted, and then the feeding is continued; and / or,

[0027] The concentration of cobalt salt in the metal salt solution is 70-100 g / L, the concentration of nickel salt is 10-50 g / L, the concentration of manganese salt is 1-5 g / L, and the concentration of aluminum salt is 0.8-1.2 g / L;

[0028] Preferably, the carbonate solution contains at least one of ammonium bicarbonate, sodium bicarbonate and sodium carbonate.

[0029] The third aspect of the present invention provides a lithium cobalt oxide positive electrode material, which is prepared by sintering a precursor material and a lithium source. The precursor material is the modified cobalt oxide precursor material provided in the first aspect or the modified cobalt oxide precursor material prepared by the preparation method provided in the second aspect.

[0030] A fourth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium cobalt oxide positive electrode material provided in the third aspect.

[0031] By applying the technical solution of the present invention, by doping aluminum, nickel and manganese elements and limiting the doping of high content of nickel and manganese elements, the high voltage requirement of the lithium cobalt oxide positive electrode material prepared with the precursor material can be met, and the lattice structure of the precursor material can be stabilized. At the same time, by limiting the D50 particle size, specific surface area and SPAN value of the precursor material, the particle size can be uniform, the particle surface is free of cracks, the stress between the particles is reduced, the risk of particle breakage is reduced, and the electrochemical reaction of the lithium cobalt oxide positive electrode material prepared with the precursor material during the charging and discharging process is prevented from being uneven, the capacity decay is slowed down, and it is helpful to improve the cycle life of the positive electrode material under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 This is a 500-fold SEM image of the modified cobalt tetroxide precursor material of Example 1 of the present invention;

[0034] Figure 2 This is a 1000-fold SEM image of the modified cobalt tetroxide precursor material of Example 1 of the present invention;

[0035] Figure 3 This is a 500-fold SEM image of the modified cobalt tetroxide precursor material of Comparative Example 1 of the present invention;

[0036] Figure 4 This is a 1000-fold SEM image of the modified cobalt tetroxide precursor material of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0038] As described in the background technology, the existing lithium cobalt oxide positive electrode materials have the problem of greatly reduced cycle life and cycle stability under high voltage conditions. In order to solve the above technical problems, the present invention provides a modified cobalt tetroxide precursor material, which includes a cobalt tetroxide matrix and nickel, manganese and aluminum elements doped into the cobalt tetroxide matrix; among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of nickel is 5% to 20%, the molar proportion of manganese is 1% to 3%, and the molar proportion of aluminum is 0.8% to 3%. The D50 particle size of the modified cobalt tetroxide precursor material is 15 to 20 μm, and the specific surface area is 3 to 5 m 2 / g, and the particle size distribution width SPAN value of the modified cobalt tetroxide precursor material is 0.2-0.4.

[0039] Aluminum, nickel and manganese as doping elements can replace the position of cobalt or oxygen in the cobalt oxide lattice, thereby changing the physical and chemical properties of the material. Specifically, by doping with aluminum, cobalt oxide can have a high operating voltage, and by limiting the doping of nickel, the segregation caused by aluminum doping in the precursor during the preparation process can be avoided, providing higher capacity and taking into account high operating voltage. By doping with nickel and manganese, the phase change can be converted into solid solution behavior, inhibiting the phase change during the charge and discharge process, and improving the structural stability of the lattice.

[0040] In the modified cobalt oxide precursor material of the present invention, the metal elements of the modified cobalt oxide precursor material include cobalt, nickel, manganese and aluminum. Among these four elements, the molar proportion of nickel is 5% to 20%, such as 5%, 8%, 10%, 12%, 13%, 15%, 18%, 20% or any two of them. By limiting the doping of high nickel elements, the segregation caused by the doping of aluminum in the precursor during the preparation process can be avoided, and the structural stability of the precursor material can be further improved while providing a higher capacity, avoiding the generation of more small particles and cracking during the sintering process. At the same time, the molar proportion of manganese is 1% to 3%, such as 1%, 2%, 3% or any two of them. The molar proportion of aluminum is 0.8% to 3%, such as 0.8%, 0.9%, 1%, 2%, 3% or any two of them. By doping aluminum, nickel and manganese elements and limiting the doping to specific contents of nickel, manganese and aluminum elements, the high voltage requirement of the lithium cobalt oxide positive electrode material prepared from the precursor material can be met, and at the same time, the lattice structure of the precursor material can be stabilized, thereby helping to improve the cycle stability of the lithium cobalt oxide positive electrode material prepared from the precursor material under high voltage.

[0041] D50 particle size refers to the particle size corresponding to when the cumulative particle size percentage reaches 50%, that is, particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it account for 50%. The D50 particle size can be obtained by testing with a particle size analyzer. Specific surface area refers to the surface area per unit mass of the precursor material. A small specific surface area indicates that there is no cracking on the particle surface and the sphericity is good. By simultaneously limiting the D50 particle size and specific surface area of ​​the precursor material, it is possible to ensure uniform particle size, no cracking on the particle surface, reduce stress between particles, reduce the risk of particle breakage, prevent uneven electrochemical reactions of the lithium cobalt oxide positive electrode material prepared with the precursor material during the charge and discharge process, slow down capacity decay, and help improve the cycle life of the positive electrode material under high voltage.

[0042] The particle size distribution width SPAN value of the modified cobalt oxide precursor material of the present invention is 0.2 to 0.4. By limiting the particle size distribution width SPAN value of the modified cobalt oxide precursor material within an appropriate range, the particle size distribution width is relatively concentrated, so that the particle size of the subsequently prepared lithium cobalt oxide positive electrode material can be uniform, providing a higher energy density.

[0043] Specifically, the particle size distribution width SPAN value is calculated according to the formula (D90-D10) / D50, D10 is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 10%, D50 is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 50%, and D90 is the particle size corresponding to when the volume cumulative distribution percentage of the sample reaches 90%.

[0044] The present invention does not limit the test method of the above D10, D50, and D90, and for example, a laser particle size analyzer may be used for measurement.

[0045] In some preferred embodiments, the molar proportion of nickel in the metal elements of the modified cobalt tetroxide precursor material is 12% to 20%.

[0046] The present invention does not limit the molar ratio of other doping elements except nickel, and can be adjusted according to actual needs. For example, in some embodiments,

[0047] Among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of cobalt element is 60% to 95%, for example, 60%, 62%, 64%, 66%, 68%, 70%, 80%, 85%, 90%, 95% or any two thereof. By limiting the molar proportion of cobalt element to the above range, while ensuring the lattice structure of lithium cobalt oxide prepared from the precursor material, the electrochemical performance is significantly improved, and at the same time, the cobalt content in lithium cobalt oxide can be reduced by doping, thereby reducing production costs.

[0048] The tap density refers to the degree of compaction of the precursor material within a unit volume, which can reflect the compaction performance of the precursor material. The tap density of the precursor material directly affects the energy storage capacity of the positive electrode material prepared from the precursor material. Appropriate tap density means that the particles of the positive electrode material have better contact, which helps to improve the electronic conduction performance.

[0049] In some embodiments, the tap density of the modified cobalt oxide precursor material is 2 to 3 g / cm 3 , which can enable it to form a uniform lithium cobalt oxide positive electrode material during the sintering process, which helps to improve both cycle stability and energy density.

[0050] Specifically, the particle size distribution width of the modified cobalt oxide precursor material is calculated according to the formula (D90-D10) / D50, where D10 is the particle size corresponding to 10% of the cumulative volume distribution percentage of the sample, D50 is the particle size corresponding to 50% of the cumulative volume distribution percentage of the sample, and D90 is the particle size corresponding to 90% of the cumulative volume distribution percentage of the sample.

[0051] The present invention does not limit the test method of D10, D50 and D90 of the modified cobalt tetroxide precursor material. For example, a laser particle size analyzer may be used for measurement.

[0052] The present invention does not limit the specific values ​​of D10 and D90. For example, in some embodiments, the D10 of the modified cobalt oxide precursor material is 10-15 μm, and the D90 is 15-20 μm. By limiting the particle size to meet the above requirements, the particle size distribution width SPAN of the modified cobalt oxide precursor material can be within the above range, thereby improving the compaction density, and preventing the particles from cracking during stress and circulation.

[0053] In some preferred embodiments, the molar ratio of nickel in the modified cobalt oxide precursor material is 13% to 19%, the molar ratio of manganese is 2.5 to 3%, and the molar ratio of aluminum is 0.8% to 0.9%; the D50 particle size of the modified cobalt oxide precursor material is 16 to 17 μm; the tap density of the modified cobalt oxide precursor material is 2.6 to 2.7 g / cm 3 , which helps to further improve the cycle stability and energy density.

[0054] The present invention does not limit the specific chemical formula of the modified cobalt oxide precursor material, and can be adjusted and obtained according to actual needs. For example, in some embodiments, the chemical formula of the modified cobalt oxide precursor material is (Co x Ni y Mn y Al k)3O4, wherein: x+y+z+k=1, 0.76≤x≤0.92, 0.05≤y≤0.2, 0.01≤z≤0.03, 0.02≤k≤0.03.

[0055] In some preferred embodiments, among the metal elements in the modified cobalt tetroxide precursor material, the molar ratio of cobalt element is 76.2% to 81.8%, the molar ratio of nickel element is 12.7% to 18.6%, the molar ratio of manganese element is 2.8% to 3%, and the molar ratio of aluminum element is 2.3% to 2.6%; and / or, the D50 particle size of the modified cobalt tetroxide precursor material is 16 to 17 μm; and / or, the tap density of the modified cobalt tetroxide precursor material is 2.6 to 2.7 g / cm 3 ; and / or, the specific surface area of ​​the modified cobalt tetroxide precursor material is 3.8 to 4 m 2 / g; and / or, the SPAN value of the modified cobalt tetroxide precursor material is 0.28-0.32.

[0056] The second aspect of the present invention provides a method for preparing a modified cobalt oxide precursor material, which is characterized in that it includes the following steps: S1, respectively adding a metal salt solution and a carbonate solution to a reaction base liquid, and adopting a first method of reducing the speed to perform nucleation to obtain a first reaction liquid; wherein the D50 particle size of the solid phase material in the first reaction liquid is 8 to 12 μm; S2, adding a metal salt solution and a carbonate solution to the first reaction liquid, and adopting a second method of reducing the speed flow rate to perform growth to obtain a second reaction liquid; wherein the D50 particle size of the solid phase material in the second reaction liquid is 20 to 25 μm; S3, washing, centrifuging and drying the second reaction liquid in sequence to obtain a dry product; and sintering the dry product at a high temperature to obtain a modified cobalt oxide precursor material; wherein the metal salt solution contains cobalt salt, aluminum salt, nickel salt and manganese salt.

[0057] S1 is the nucleation stage of modified cobalt carbonate, and S2 is the growth stage of modified cobalt carbonate. Among them, cobalt salt, aluminum salt, nickel salt, manganese salt in the metal salt solution reacts with carbonate to form modified cobalt carbonate, and the modified cobalt carbonate includes a cobalt carbonate matrix and aluminum elements, nickel elements and manganese elements doped into the cobalt carbonate matrix. S3 is essentially a process of sintering modified cobalt carbonate to form a modified cobalt oxide precursor material. Among them, the cobalt salt can be at least one of cobalt chloride, cobalt sulfate, and cobalt nitrate, and the aluminum salt, nickel salt, and manganese salt can be chlorides, sulfates, or nitrates corresponding to soluble aluminum, nickel, and manganese.

[0058] The preparation method of the modified cobalt tetroxide precursor material provided by the present invention realizes the preparation of large-particle high-nickel-manganese cobalt tetroxide through the coordinated cooperation between various parameters in the preparation process, and the various parameters influence each other, and the uniform distribution of doping elements, the regulation of particle sphericity and particle crystallinity all play a decisive role. Specifically, the nucleation stage and the growth stage are respectively implemented by the first reduction of the speed and the second reduction of the speed flow rate, which can achieve uniform dispersion, make the doping elements evenly distributed, and can also effectively control the morphology, so that the sphericity of the shape is good, the particle size uniformity is good, and it is conducive to obtaining a precursor material whose D50 particle size meets the above requirements. At the same time, combined with the temperature increase sintering method, the particle crystallinity is enhanced to ensure that there is no obvious cracking phenomenon on the particle surface, which is conducive to obtaining a precursor material whose specific surface area meets the above requirements, and the lithium cobalt oxide positive electrode material prepared by the precursor material has excellent cycle stability and cycle life.

[0059] During the nucleation and growth process, it is necessary to assist with the stirring speed. The first speed reduction means that the speed continues to decrease as the nucleation reaction proceeds. In some embodiments, the first speed reduction is that the D50 particle size of the solid phase material in the reaction solution increases by 1.5 to 2.0 μm, and the speed decreases by 20 rpm. Specifically, during the nucleation process, the initial speed is V0, when the D50 particle size of the solid phase material in the reaction solution is D0, the speed is V0-20 rpm, when the D50 particle size of the solid phase material in the reaction solution is D0+△D, the speed is V0-40 rpm, when the D50 particle size of the solid phase material in the reaction solution is D0+2△D, the speed is V0-60 rpm, and so on, when the D50 particle size of the solid phase material in the reaction solution is D0+N△D, the speed is V0-N×20 rpm. Wherein, D0 is 1.5 to 2.0 μm, △D is 1.5 to 2.0 μm, and N is a natural integer.

[0060] The first speed reduction means that as the nucleation reaction proceeds, the speed continues to decrease, and the flow rate of the metal salt solution continues to decrease. In some embodiments, the second speed reduction flow rate is that for every 1-1.5 μm increase in the D50 particle size of the solid phase material in the reaction solution, the speed decreases by 15 rpm, and the flow rate of the metal salt solution decreases by 10 mL / min. Specifically, during the nucleation process, the initial rotation speed is V1, the initial flow rate of the metal salt solution is V2, when the D50 particle size of the solid phase material in the reaction solution is L0, the rotation speed is V1-15rpm, the flow rate of the metal salt solution is V2-10mL / min, when the D50 particle size of the solid phase material in the reaction solution is L0+△L, the rotation speed is V1-30rpm, the flow rate of the metal salt solution is V2-20mL / min, when the D50 particle size of the solid phase material in the reaction solution is L0+2△L, the rotation speed is V1-45rpm, the flow rate of the metal salt solution is V2-30mL / min, and so on, when the L50 particle size of the solid phase material in the reaction solution is L0+N△L, the rotation speed is V1-N×15rpm, and the flow rate of the metal salt solution is V2-N×10mL / min. Wherein, L0 is 1 to 1.5μm, △L is 1 to 1.5μm, and N is a natural integer.

[0061] The present invention does not limit the specific values ​​of the rotation speed and flow rate during the nucleation and growth process, as long as the changes are guaranteed. For example, in some embodiments, during the nucleation process, the rotation speed is 150-250 rpm, and the flow rate of the metal salt solution is 10-40 mL / min; during the growth process, the rotation speed is 80-150 rpm, and the flow rate of the metal salt solution is 10-60 mL / min.

[0062] In some embodiments, during the nucleation process, the reaction temperature is 35-45°C, and the pH value is controlled to be 7.5-8.5; and / or, during the growth process, the reaction temperature is 35-45°C, and the pH value is controlled to be 7-8; and / or, the pH value of the reaction base liquid is 7-9. By limiting the pH value of the reaction base liquid to 7-9 and the pH value of the nucleation process to 7.5-8.5, a large number of crystal nuclei are formed. After the crystal nuclei are formed, the formation of small particles and the particle size growth rate can be controlled by controlling the pH value to 7-8 during the growth process to ensure the growth rate of the particles, thereby obtaining a modified cobalt trioxide precursor material that meets the above requirements.

[0063] The pH value can be controlled by adjusting the flow rate and addition amount of the carbonate solution. The present invention does not limit the feeding flow rate of the carbonate solution, as long as the pH value of the reaction bottom solution is 7.5-8.5, the pH value of the nucleation process is 7.5-8.5, and the pH value of the growth process is 7-8.

[0064] In some preferred embodiments, the D50 particle size of the solid phase material in the first reaction liquid is 8.5-9.5 μm; the D50 particle size of the solid phase material in the second reaction liquid is 20-22 μm.

[0065] Temperature-increasing sintering refers to sintering under conditions of increasing temperature. For example, in some embodiments, the temperature-increasing sintering is performed in the first temperature zone, the second temperature zone, and the third temperature zone in sequence; the temperature of the third temperature zone> the temperature of the second temperature zone> the temperature of the first temperature zone. It can also be understood that the dried product is sintered in the first temperature zone, the second temperature zone, and the third temperature zone in sequence. By setting a three-stage temperature-increasing sintering, it is helpful to complete the sintering, ensure the crystallinity of the modified cobalt oxide precursor material, prevent cracking of the particle surface, and further improve the electrochemical performance of the positive electrode material made from the precursor material.

[0066] The present invention does not limit the specific temperatures of the first temperature zone, the second temperature zone and the third temperature zone and the residence time in each temperature zone, which can be adjusted according to actual needs. In some preferred embodiments, the temperature of the first temperature zone is 300-450°C, the temperature of the second temperature zone is 450-600°C, and the temperature of the third temperature zone is 780-820°C.

[0067] Specifically, the temperature-raising sintering can be implemented in a rotary kiln. At this time, the frequency of the rotary kiln is 7.5HZ, and the feeding rate of the dried product is 10-11kg / h, or, the feeding rate is 5kg / h according to the metal mass.

[0068] The above preparation method can be implemented in a reactor, for example, a conventional reactor in the art. In some embodiments, the metal salt solution and the carbonate solution are fed through the upper and lower parallel flow of the reactor. Different feeding points can distribute the raw materials more evenly, reduce the problem of excessive or low local concentration, and at the same time, the utilization rate of the material can be improved by feeding in parallel. The present invention ensures that the metal salt solution and the carbonate solution are fully in contact by adopting the upper and lower parallel flow feeding method, which is conducive to achieving uniform distribution of doping elements.

[0069] During the nucleation and growth process, in order to ensure that there is enough space in the reactor, it is necessary to stop feeding at regular intervals, extract part of the supernatant, and then continue feeding. In some embodiments, during the nucleation and growth process, when the total volume of the reaction liquid reaches 80% to 90% of the reactor volume, stop feeding, extract part of the supernatant, and then continue feeding. For example, when the volume of the reactor is 50L, when the reaction liquid reaches 40 to 50L, stop feeding, extract part of the supernatant, and then continue feeding, wherein the volume of part of the supernatant can be 40% to 60% of the total reaction liquid volume, which can be adjusted according to actual conditions, and the present invention does not make too many restrictions here.

[0070] The present invention can adopt the volume addition method to prepare the metal salt solution. Specifically, first prepare a high concentration of nickel salt solution and manganese salt solution, and then add cobalt salt solution, nickel salt solution and manganese salt solution by volume, and aluminum salt can be directly added in solid form. Specifically, different masses of nickel salt, cobalt salt and manganese salt can be selected according to the stoichiometric ratio. In addition, it should be noted that the mass of nickel salt and manganese salt needs to be added according to a certain ratio coefficient, and the mass ratio of nickel salt to cobalt salt is (1.3-1.4):1, and the mass ratio of manganese salt to cobalt salt is (1.0-1.1):1.

[0071] The present invention does not limit the concentration of each metal in the metal salt solution, but is adjusted according to the chemical formula ratio required for actual production. For example, the concentration of cobalt salt in the metal salt solution is 70-100 g / L, the concentration of nickel salt is 10 g / L-50 g / L, the concentration of manganese salt is 1 g / L-5 g / L, and the concentration of aluminum salt is 0.8-1.2 g / L. The carbonate solution contains carbonate, and the carbonate includes at least one of ammonium bicarbonate, sodium bicarbonate, and sodium carbonate. The concentration of carbonate in the carbonate solution is 200-250 g / L, preferably 221-231 g / L.

[0072] The reaction base liquid can be a mixture of water and carbonate solution, wherein the volume ratio of water to carbonate solution is (5-8):1.

[0073] In S2, the first reaction liquid can be divided into multiple parts for growth, for example, part of the first reaction liquid can be transferred to a growth reactor for growth to achieve continuous preparation, wherein the volume proportion of the part of the first reaction liquid is 40% to 60%.

[0074] In S3, during the washing process, the volume ratio of the second reaction liquid to the washing water is (5-7):1, and the washing time is 10-20 minutes. Drying can be performed by oven drying or flash evaporation for rapid drying, with a drying temperature of 80-150° C. and a time of 6-10 hours.

[0075] The third aspect of the present invention provides a lithium cobalt oxide positive electrode material, which is prepared by sintering a precursor material and a lithium source. The precursor material is the modified cobalt oxide precursor material provided in the first aspect or the modified cobalt oxide precursor material prepared by the preparation method provided in the second aspect.

[0076] Specifically, the modified cobalt oxide precursor material can be directly subjected to lithiation sintering treatment to obtain a lithium cobalt oxide positive electrode material. Since the modified cobalt oxide precursor material having specific doping elements and physicochemical properties is used for sintering, a lithium cobalt oxide positive electrode material having excellent cycle stability and cycle life under high voltage conditions can be obtained.

[0077] A fourth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium cobalt oxide positive electrode material provided by the third invention.

[0078] Due to the inclusion of the lithium cobalt oxide positive electrode material with excellent performance, the battery assembled from the positive electrode material has excellent cycle stability and cycle life under high voltage conditions.

[0079] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0080] Example 1

[0081] The preparation method of the modified cobalt trioxide precursor material of this embodiment includes:

[0082] (1) Solution preparation: cobalt salt, aluminum salt, nickel salt, manganese salt and water are mixed to obtain a metal salt solution; the concentration of cobalt salt in the metal salt solution is 89.44 g / L, the concentration of nickel salt is 29.39 g / L, the concentration of manganese salt is 3.63 g / L, and the concentration of aluminum salt is 1.27 g / L; wherein the cobalt salt, aluminum salt, nickel salt and manganese salt are cobalt sulfate, aluminum sulfate, nickel sulfate and manganese sulfate, respectively;

[0083] (2) Seed stage: 1L of ammonium bicarbonate solution (wherein the concentration of ammonium bicarbonate is 225.5g / L) and 6L of water are added to a 50L pusher reactor to form a reaction bottom liquid, so that the reaction bottom liquid submerges the first layer of stirring paddles. Under continuous stirring, the pH value of the reaction bottom liquid reaches 9.0, and then a peristaltic pump is used to pump the metal salt solution and the ammonium bicarbonate solution into the reactor. The metal salt solution and the ammonium bicarbonate solution are fed in parallel in two ways, the reaction temperature is 40°C, the pH value is 8.5, the initial stirring speed is 250rpm, and the flow rate of the metal salt solution is 30mL / min. During the feeding process, the feeding is stopped after the total volume of the reaction liquid reaches 40-45L, and part of the supernatant is extracted after standing. Then, the feeding is circulated for growth. The rotation speed decreases by 20rpm for every 1.5-2.0μm increase in the D50 particle size of the solid material in the reaction system until the D50 particle size of the solid phase material in the reaction system reaches 8.5-9.5μm, thereby obtaining a first reaction liquid;

[0084] (3) Growth stage: 20 L of the first reaction liquid was transferred into a 50 L frame reactor as the bottom liquid of the growth stage, and the metal salt solution and the carbonate solution were added thereto respectively. The reaction temperature was 35 °C, the pH value was 7.8, the initial stirring speed was 150 rpm, and the initial flow rate of the metal salt solution was 50 mL / min. During the feeding process, the feeding was stopped after the total volume of the reaction liquid reached 40-45 L. After standing, part of the supernatant was extracted, and then the feeding was circulated for growth. The particle size of the solid material D50 in the reaction system increased by 1-1. 5μm, the rotation speed decreases by 15rpm, and the flow rate of the metal salt solution decreases by 10mL / min; the specific setting is: for example, when the particle size is 9.5-13.2μm, the flow rate of the metal salt solution is 30-50mL / min; when the particle size is 13.2-17.5μm, the flow rate is 15-35mL / min; when the particle size is 17.5-22μm, the flow rate is 10-20mL / min, and so on, until the D50 particle size of the solid phase material in the reaction liquid reaches 20-22μm, and the second reaction liquid is obtained;

[0085] (4) washing and drying: the second reaction liquid is transferred into a centrifuge, and washed and dehydrated according to a volume ratio of the second reaction liquid to washing water of 6:1, the washing time is 20 minutes, and then dried in a blast drying oven at 120° C. to obtain a spherical cobalt carbonate powder material;

[0086] (5) Sintering: The washed and dried spherical cobalt carbonate powder material is sintered in the low temperature zone, medium temperature zone and high temperature zone of a rotary kiln in sequence, wherein the temperature of the low temperature zone is 350°C, the temperature of the medium temperature zone is 500°C, and the temperature of the high temperature zone is 820°C, to obtain a modified cobalt oxide precursor material.

[0087] Example 2

[0088] The preparation method of the modified cobalt trioxide precursor material of this embodiment includes:

[0089] (1) Solution preparation: cobalt salt, aluminum salt, nickel salt, manganese salt and water are mixed to obtain a metal salt solution; the concentration of cobalt salt in the metal salt solution is 93.84 g / L, the concentration of nickel salt is 24.04 g / L, the concentration of manganese salt is 4.12 g / L, and the concentration of aluminum salt is 1.39 g / L; wherein the cobalt salt, aluminum salt, nickel salt and manganese salt are cobalt sulfate, aluminum sulfate, nickel sulfate and manganese sulfate, respectively;

[0090] (2) Seed stage: 1L of ammonium bicarbonate solution (the concentration of ammonium bicarbonate is 226.3g / L) and 6L of water are added to a 50L pusher reactor to form a reaction base liquid, so that the reaction liquid just submerges the first layer of stirring paddles. Under continuous stirring, the pH value of the reaction base liquid reaches 8.5, and then a peristaltic pump is used to pump the metal salt solution and ammonium bicarbonate solution into the reactor. The metal salt solution and ammonium bicarbonate solution are fed in parallel in two ways, the reaction temperature is 38°C, the pH value is 8.0, the initial stirring speed is 250rpm, and the flow rate of the metal salt solution is 40mL / min. During the feeding process, the feeding is stopped after the total volume of the reaction liquid reaches 40-45L, and part of the supernatant is extracted after standing. Then, the feeding is circulated for growth. The rotation speed decreases by 20rpm for every 1.5-2.0μm increase in the D50 particle size of the solid material in the reaction system until the D50 particle size of the solid phase material in the reaction liquid reaches 8.5-9.5μm, thereby obtaining a first reaction liquid;

[0091] (3) Growth stage: 20 L of the first reaction liquid was transferred into a 50 L frame reactor as the bottom liquid of the growth stage, and the metal salt solution and the carbonate solution were added thereto respectively. The reaction temperature was 35 ° C, the pH value was 7.5, the initial stirring speed was 150 rpm, and the initial flow rate of the metal salt solution was 60 mL / min. During the feeding process, the feeding was stopped after the total volume of the reaction liquid reached 40 to 45 L. After standing, part of the supernatant was extracted, and then the feeding was circulated for growth. The particle size of the solid material D50 in the reaction system increased by 1 to 1.5 μm. m, the speed decreases by 15 rpm, and the flow rate of the metal salt solution decreases by 10 mL / min; the specific setting is: for example, when the particle size is 9.5-13.2 μm, the flow rate of the metal salt solution is 30-60 mL / min; when the particle size is 13.2-17.5 μm, the flow rate is 20-35 mL / min; when the particle size is 17.5-22 μm, the flow rate is 10-20 mL / min, and so on, until the D50 particle size of the solid phase material in the reaction liquid reaches 20-22 μm, and a second reaction liquid is obtained;

[0092] (4) washing and drying: the second reaction liquid is transferred into a centrifuge, and washed and dehydrated according to a volume ratio of the second reaction liquid to washing water of 6:1, the washing time is 20 minutes, and then dried in a blast drying oven at 120° C. to obtain a spherical cobalt carbonate powder material;

[0093] (5) Sintering: The washed and dried spherical cobalt carbonate powder material is sequentially sintered in the low temperature zone, medium temperature zone, and high temperature zone of a rotary kiln, wherein the temperature of the low temperature zone is 300°C, the temperature of the medium temperature zone is 450°C, and the temperature of the high temperature zone is 800°C, to obtain a modified cobalt trioxide precursor material (Co 0.762 Ni 0.186 Mn 0.029 Al 0.023 )3O4.

[0094] Comparative Example 1

[0095] The preparation method of the modified cobalt tetroxide precursor material in this comparative example comprises:

[0096] (1) Solution preparation: cobalt salt, aluminum salt, nickel salt, manganese salt and water are mixed to obtain a metal salt solution; the concentration of cobalt salt in the metal salt solution is 89.44 g / L, the concentration of nickel salt is 29.39 g / L, the concentration of manganese salt is 3.63 g / L, and the concentration of aluminum salt is 1.27 g / L; wherein the cobalt salt, aluminum salt, nickel salt and manganese salt are cobalt sulfate, aluminum sulfate, nickel sulfate and manganese sulfate, respectively;

[0097] (2) Seed stage: 1L of ammonium bicarbonate solution (wherein the concentration of ammonium bicarbonate is 226g / L) and 6L of water are added to a 50L pusher reactor to form a reaction bottom liquid, so that the reaction bottom liquid submerges the first layer of stirring paddles. Under continuous stirring, the pH value of the reaction bottom liquid reaches 9.0, and then a peristaltic pump is used to pump the metal salt solution and the ammonium bicarbonate solution into the reactor. The metal salt solution and the ammonium bicarbonate solution are fed in parallel in an upper and lower manner. The reaction temperature is 40°C, the pH value is 8.5, the stirring speed is 200rpm, and the flow rate of the metal salt solution is 30mL / min. During the feeding process, the feeding is stopped after the total volume of the reaction liquid reaches 40-45L, and a portion of the supernatant is extracted after standing. Then, the feeding is circulated for growth until the D50 particle size of the solid phase material in the reaction liquid reaches 8.5-9.5μm, thereby obtaining a first reaction liquid;

[0098] (3) Growth stage: 20 L of the first reaction liquid was transferred to a 50 L frame kettle as the bottom liquid of the growth stage, and the metal salt solution and the carbonate solution were added thereto respectively. The reaction temperature was 38 ° C., the flow rate of the metal salt solution was 30 mL / min, the pH value of the reaction system was 7.8, and the stirring speed was 130 rpm. During the feeding process, the feeding was stopped after the total volume of the reaction liquid reached 40 to 45 L. After standing, part of the supernatant was extracted, and then the feeding was circulated for growth. When the D50 of the solid material in the reaction system reached 12 to 15 μm, the kettle was split and the growth was continued to the target particle size of 15 to 18 μm to obtain the final reaction liquid.

[0099] (4) Washing and drying: The final reaction liquid is transferred to a centrifuge, and washed and dehydrated according to a volume ratio of reaction liquid to washing water of 6:1. The washing time is 20 minutes. Subsequently, the dehydrated cobalt carbonate is placed in a tray and dried in a forced air drying oven at 120° C. to obtain a spherical cobalt carbonate powder material.

[0100] (5) Sintering: The spherical cobalt carbonate powder material is sintered in the low temperature zone and the high temperature zone of the rotary kiln in turn, with the temperature of the low temperature zone being 500°C and the temperature of the high temperature zone being set to 820°C to obtain a modified cobalt trioxide precursor material (Co0.818 Ni 0.127 Mn 0.029 Al 0.026 )3O4.

[0101] Comparative Example 2

[0102] The difference from Example 1 is that during the growth stage, the rotation speed and flow rate remain unchanged.

[0103] Test example

[0104] 1. D50 particle size

[0105] The particle size of the modified cobalt tetroxide precursor material was tested using a particle size analyzer.

[0106] 2. Specific surface area

[0107] The specific surface area was measured by nitrogen adsorption method (BET method).

[0108] 3. Tap density

[0109] Put the powder sample into a container with a volume of V, and put the container with the powder sample into a vibrating screen. The vibration frequency of the vibrating screen is between 100 Hz, the amplitude is 4 mm, and the vibration time is usually between 5 minutes. Take the container and the powder sample out of the vibrating screen, and use the electronic balance to measure the mass m of the powder sample after vibration again. Divide the mass m of the powder sample after vibration by the volume V of the container to obtain the tap density. Test multiple times and take the average value.

[0110] Table 1

[0111]

[0112] according to Figures 1 to 4 It can be seen that the modified cobalt oxide precursor material of the present invention has good particle sphericity, uniform particle size, no small particles, and no cracks on the surface, while the modified cobalt oxide precursor material of Comparative Example 1 has a large number of small particles, and some particles have cracks on the surface.

[0113] The modified cobalt oxide precursor material of the present invention can be uniformly doped with aluminum, nickel and manganese elements, as well as doped with a high nickel content. The lithium cobalt oxide positive electrode material prepared from the precursor material of the present invention can meet higher voltage requirements and greatly improve the cycle stability and cycle life of the lithium cobalt oxide positive electrode material under high voltage conditions (4.5V).

[0114] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those described herein, for example.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified cobalt tetroxide precursor material, characterized in that: The modified cobalt tetroxide precursor material comprises a cobalt tetroxide matrix and nickel, manganese and aluminum elements doped into the cobalt tetroxide matrix; wherein, among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of nickel is 5% to 20%, the molar proportion of manganese is 1% to 3%, and the molar proportion of aluminum is 0.8% to 3%. The D50 particle size of the modified cobalt tetroxide precursor material is 15 to 20 μm, and the specific surface area is 3 to 5 m 2 / g, and the particle size distribution width SPAN value of the modified cobalt trioxide precursor material is 0.2-0.

4.

2. The modified cobalt trioxide precursor material according to claim 1, characterized in that: Among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of nickel element is 12% to 20%; and / or, among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of cobalt element is 60% to 95%; and / or, the tap density of the modified cobalt tetroxide precursor material is 2 to 3 g / cm 3 .

3. The modified cobalt trioxide precursor material according to claim 1, characterized in that: The chemical formula of the modified cobalt tetroxide precursor material is (Co x Ni y Mn y Al k )3O4, where , satisfying: x+y+z+k=1, 0.76≤x≤0.92, 0.05≤y≤0.2, 0.01≤z≤0.03, 0.02≤k≤0.

03.

4. The modified cobalt trioxide precursor material according to claim 2, characterized in that: Among the metal elements in the modified cobalt tetroxide precursor material, the molar proportion of cobalt element is 76.2% to 81.8%, the molar proportion of nickel element is 12.7% to 18.6%, the molar proportion of manganese element is 2.8% to 3%, and the molar proportion of aluminum element is 2.3% to 2.6%; and / or, the D50 particle size of the modified cobalt tetroxide precursor material is 16 to 17 μm; and / or, the tap density of the modified cobalt tetroxide precursor material is 2.6 to 2.7 g / cm 3 ; and / or, the specific surface area of ​​the modified cobalt oxide precursor material is 3.8 to 4 m 2 / g; and / or, the SPAN value of the modified cobalt oxide precursor material is 0.28-0.

32.

5. A method for preparing the modified cobalt trioxide precursor material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, respectively adding a metal salt solution and a carbonate solution into a reaction base liquid, and performing nucleation by a first speed reduction method to obtain a first reaction liquid; wherein the D50 particle size of the solid phase material in the first reaction liquid is 8 to 12 μm; S2, adding the metal salt solution and the carbonate solution to the first reaction solution, and growing them in a second manner of reducing the rotation speed and flow rate to obtain a second reaction solution; wherein the D50 particle size of the solid phase material in the second reaction solution is 20 to 25 μm; S3, washing, centrifuging and drying the second reaction liquid in sequence to obtain a dry product; sintering the dry product at a high temperature to obtain the modified cobalt tetroxide precursor material; Wherein, the metal salt solution contains cobalt salt, aluminum salt, nickel salt and manganese salt.

6. The preparation method according to claim 5, characterized in that: The first speed reduction is that the speed decreases by 20 rpm for every 1.5-2.0 μm increase in the D50 particle size of the solid phase material in the reaction solution; The second speed reduction flow rate is that the speed decreases by 15 rpm and the flow rate of the metal salt solution decreases by 10 mL / min for every 1-1.5 μm increase in the D50 particle size of the solid phase material in the reaction solution; Preferably, during the nucleation process, the rotation speed is 150 to 250 rpm, and the flow rate of the metal salt solution is 10 to 40 mL / min; Preferably, during the growth process, the rotation speed is 80 to 150 rpm, and the flow rate of the metal salt solution is 10 to 60 mL / min; Preferably, during the nucleation process, the reaction temperature is 35-45°C and the pH value is controlled to be 7.5-8.5; Preferably, during the growth process, the reaction temperature is 35-45°C and the pH value is controlled to be 7-8; Preferably, the pH value of the reaction base solution is 7 to 9; Preferably, the D50 particle size of the solid phase material in the first reaction solution is 8.5 to 9.5 μm; Preferably, the D50 particle size of the solid phase material in the second reaction liquid is 20-22 μm.

7. The preparation method according to claim 5, characterized in that: The temperature-raising sintering is to perform sintering in the first temperature zone, the second temperature zone and the third temperature zone in sequence; the temperature of the third temperature zone is greater than the temperature of the second temperature zone and greater than the temperature of the first temperature zone; Preferably, the temperature of the first temperature zone is 300-450°C, the temperature of the second temperature zone is 450-600°C, and the temperature of the third temperature zone is 780-820°C.

8. The preparation method according to claim 6, characterized in that: The metal salt solution and the carbonate solution are fed in parallel through the upper and lower paths of the reactor; and / or, During the nucleation and growth process, when the total volume of the reaction liquid reaches 80% to 90% of the reactor volume, the feeding is stopped, part of the supernatant is extracted, and then the feeding is continued; and / or, The concentration of cobalt salt in the metal salt solution is 70-100 g / L, the concentration of nickel salt is 10-50 g / L, the concentration of manganese salt is 1-5 g / L, and the concentration of aluminum salt is 0.8-1.2 g / L; Preferably, the carbonate solution contains at least one of ammonium bicarbonate, sodium bicarbonate and sodium carbonate.

9. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide positive electrode material is prepared by sintering a precursor material and a lithium source, and the precursor material is the modified cobalt tetroxide precursor material according to any one of claims 1 to 4 or the modified cobalt tetroxide precursor material prepared by the preparation method according to any one of claims 5 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium cobalt oxide positive electrode material according to claim 9.

Citation Information

Cited By

  • Wide-span lithium cobalt oxide precursor material as well as preparation method and application thereof

    CN121044634A